Ta có: \(5\sqrt{x-1}-\sqrt{36x-36}+\sqrt{9x-9}=\sqrt{8x+12}\) \(\left(ĐK:x\ge1\right)\)
\(\Leftrightarrow5\sqrt{x-1}-6\sqrt{x-1}+3\sqrt{x-1}=\sqrt{8x+12}\)
\(\Leftrightarrow2\sqrt{x-1}=\sqrt{8x+12}\)
\(\Leftrightarrow\left(2\sqrt{x-1}\right)^2=\left(\sqrt{8x+12}\right)^2\)
\(\Leftrightarrow4.\left(x-1\right)=8x+12\)
\(\Leftrightarrow4x-4=8x+12\)
\(\Leftrightarrow-4x=16\)
\(\Leftrightarrow x=-4\left(L\right)\)
Vậy \(S=\varnothing\)
\(5\sqrt{x-1}-\sqrt{36\left(x-1\right)}+\sqrt{9\left(x-1\right)}=\sqrt{4\left(2x+3\right)}\)
\(5\sqrt{x-1}-6\sqrt{x-1}+3\sqrt{x-1}=2\sqrt{2x+3}\)
\(2\sqrt{x-1}=2\sqrt{2x+3}\)
\(\sqrt{x-1}=\sqrt{2x+3}\)
\(\hept{\begin{cases}2x+3\ge0\\x-1=2x-3\end{cases}}\)
\(\hept{\begin{cases}2x\ge-3\\x-2x=-3+1\end{cases}}\)
\(\hept{\begin{cases}x\ge-\frac{3}{2}\\-x=-2\end{cases}}\)
\(\hept{\begin{cases}x\ge-\frac{3}{2}\\x=2\end{cases}}\)
\(\Rightarrow x=2\)
Bạn FL.capheny bị sai dấu 2x+3 thành 2x-3 mà ai vẫn tk đúng vậy
Á nhầm sửa lại
\(\hept{\begin{cases}2x+3\ge0\\x-1=2x+3\end{cases}}\)
\(\hept{\begin{cases}2x\ge-3\\-x=4\end{cases}}\)
\(\hept{\begin{cases}x\ge-\frac{3}{2}\\x=-4\end{cases}}\)
\(\Rightarrow x=\varnothing\)